Pelaksanaan Program SDGs Meningkatkan Kualitas dan Penjualan Umkm Amplang Berbasis Media Sosial di Kelurahan Sesumpu - Siti Rahmayuni; Pinem, Anwar Arifin; Jaya, Ekky Satria; Piyani, Henny Okta; Widiyanto, Agung; Anjani, Meisy Dwi (Yayasan Inspirasi El Burhani, 2024)
Introduction: This community service program is designed to improve the quality and sales of Amplang MSMEs in Sesumpu Village, Penajam District, by utilizing social media. Objective: Polaksar Bayah, Sesumpu Village, Penajam District Method: Training and Mentoring Result: increased income for entrepreneurs, strengthening production capacity, and improvements in business management practices carried out by participants. Thus, this program is expected to provide a significant positive impact on the development of MSMEs in the area Conclusion: The community service program implemented in Sesumpu Village has succeeded in achieving its goals in improving the quality and sales of Amplang MSMEs. Through a planned and participatory approach, this program is able to overcome various challenges faced by partners, including limited knowledge in business management and marketing